АХБОРОТ ХАВФСИЗЛИГИГА ДОИР ТУШУНЧАЛАР ТАВСИФИ (Scientific journal of the Fergana State University, 2023)
The article explains the concept of information security, its importance at the national and international levels, terms in this area.